2015
DOI: 10.4028/www.scientific.net/amm.772.183
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Nonlinear Sloshing Behaviors under Dynamic Actions

Abstract: This paper simulated the non-linear sloshing effects under typical dynamic actions. The sloshing simulation is realized with the Arbitrary Lagrangian Euleria (ALE) formulation plus bi-phase hydrodynamic biomaterial liquid gas materials. The study first investigated two dimensional (2D) sloshing problems under harmonic excitations. Through calibration studies in standard rectangular tanks, the case study demonstrated reasonable agreement with numerical results published by other researchers. The study was then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…figure 6, it is also observed that sloshing becomes violent and divergent at large excitation frequency resulting into computationally under prediction of sloshing heights. This can be due to the consideration of non-linear effects from potential equations [6]. Increase in pressure is shown in figure 9.…”
Section: Resultsmentioning
confidence: 99%
“…figure 6, it is also observed that sloshing becomes violent and divergent at large excitation frequency resulting into computationally under prediction of sloshing heights. This can be due to the consideration of non-linear effects from potential equations [6]. Increase in pressure is shown in figure 9.…”
Section: Resultsmentioning
confidence: 99%